Reflection on Social Justice, Race, Ethnicity and Identity from an Ethical Perspective - Atweh, Bill (Springer, 2011)
In these reflections, I identify complexities in few constructs that are often used in educational research, although not often critically, namely, social justice, race, ethnicity and identity. This paper suggests a non-ontological and non-epistemological approach to ethics as developed by Emmanuel Levinas as a normative means to deal with some of the complexities. In dealing with the construct of social justice, an ethical approach calls for productive research tools to not only understand exclusion but also to change situations of injustice to marginalised groups. Further, both constructs race and ethnicity can be used to identify groups of people based on their history, culture and/or lifestyles. As social constructions they have different historical origins and are open to alternative connotations, uses and abuses. An ethical perspective is useful to manage the dilemma of essentialism that group identification may lead into. Finally, the debate around the usefulness of the construct of identity raises some ethical questions about the role of research and the lived experience of its subjects. An ethical stance demands that constructs of analysis in social inquiry should not only demonstrate their utility for knowledge generation but also should demonstrate a responsibility for the construction and reconstruction of lifeworld in which academic endeavours are conducted.